2002
DOI: 10.1081/clt-120016953
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Acute Adult Poisoning in Gaziantep, Turkey

Abstract: These data provide important preliminary information on the pattern of symptomatic poisonings in this south-east part of our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
59
4
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 15 publications
25
59
4
12
Order By: Relevance
“…Acute poisoning was seen more in females constituting 64% than in males 36% in our study this is nearly same to the studies conducted in Turkey and India 6,10 and…”
Section: Discussionsupporting
confidence: 79%
“…Acute poisoning was seen more in females constituting 64% than in males 36% in our study this is nearly same to the studies conducted in Turkey and India 6,10 and…”
Section: Discussionsupporting
confidence: 79%
“…This situation is in consistent with the other studies in our country (2,15,16). However, many hospital-based studies from our country and from those conducted in the other countries have reported that majority of patients exposed to poisoning was female (3)(4)(5)(6)(7)(8)(17)(18)(19)(20) When the deaths due to poisonings are analysed, carbon monoxide is found to be the most common type of poisoning in south Marmara region, while the insecticides are the most common poison in İzmir, the Aegean region, and in Adana, the Mediterranean region of Turkey (2,15,16). The relatively higher incidence of carbon monoxide intoxication in this study was resulted from the cases that are found to be exposed to carbon monoxide originating from stove smoke driven back from chimneys by strong southwest wind, which is a common experience in our region.…”
Section: Discussionmentioning
confidence: 99%
“…Death due to poisoning has been known since time immemorial. Poisoning is a major problem all over the world although its type and the associated morbidity and mortality vary from country to country (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). According to the legal system of our country, all poisoning death cases are recorded as unnatural death and in addition, in Turkey, according to the article 89 of the Penal Code Law Judicial Procedure (12); any case of death due to suspected or obvious poisoning must undergo the medico-legal autopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Henderson et al (13) in their study with 732 patients have reported the need of mechanical ventilation as 79.5%. Further, Göksu et al (25) in their study with 179 patients have reported that 16 (8.9%) patients required mechanical ventilation, and the mean duration of mechanical ventilation of these cases was 3.81±1.12 days.…”
Section: Discussionmentioning
confidence: 99%